Gender role conflict and situational context - Banos, Noely (2017)
Gender role conflict (GRC) is thought to occur when men’s adherence to strict male gender roles create conflicts with incompatible situational demands (O’Neil, 2015). GRC has been correlated with various negative outcomes (e.g., anxiety, depression, hostility towards women and aggression; Sharpe, & Heppner, 1991; Kaplan, 1992). Though there is an abundance of correlational research, GRC research has yet to address the critiques regarding gender role adherence within different situational contexts (Addis, Mansfiel, & Syzdek, 2010). Research regarding contextual influences have begun to focus on centerfold syndrome, which examine patterns of masculinity reinforcement after men are exposed to sexualized images of females. By creating an environment in which masculinity is reinforced as depicted by centerfold syndrome (Wright, 2011), the present study examined contextuality and the impact it has on GRC. Male participants were assigned to a control or experimental condition and asked to fill out a measure for GRC and centerfold syndrome. In order to create an environment in which masculinity is reinforced participants in the experimental condition were shown 15 sexualized images of females. The analysis showed that men in the experimental condition did not have significantly higher scores across the entire gender role conflict measure or in its individual sub-scales when compared to the control conditions. Explanations for the -findings as well as future directions will be further discussed.